(untitled) (TEST XY. Critical review of studies on the representation of architecture and use of the image in science and art, 2018)
Typefaces have the power to enhance the traditional communication process activated by graphic signs. Indeed, in addition to transmitting meaning starting from the decoding of the signifier, they are able to communicate further information through the peculiarities and the recognizability of their sign. The different typographic characters suggest imagery, encourage mental connections with ideas and ideologies, and place communication within a more specific cultural, social, historical, and geographical context evoked by the graphic features of alphabetical signs. The different forms of power have always leveraged on this peculiarity of the alphabets by assuming the typographic characters design to effective form of self–representation. Power is therefore an interpretative category useful for reading the evolution of the form of the lettering, and for understanding their affirmation or oblivion. From the Roman Capitalis, called to represent the grandeur of the empire, to the fonts of the contemporary technological and economic empires, such as San Francisco designed by Apple, passing through the classic Romain du Roi wanted by Louis XIV, there are numerous episodes of mutual representation between powers and characters. If on the one hand the capacity of representation of power in the graphic signs can make the fortune of the alphabetic characters, it can also decree their decline, as in the case of the Fraktur adopted as image of Germanness, or the littori characters that have characterized the communication of political power in the Fascist Italy. Starting from the graphic and paleographic studies of Giovanni Lussu, Stanley Morrison, and Armando Petrucci, this article aims to retrace some of the most significant episodes of the relations between lettering and power in the western culture, updating this approach to the new forms of power of contemporary society, analyzing the graphic features of the different old and new characters of power.